Evaluasi Peningkatan Pengetahuan tentang Menopause melalui Edukasi Kesehatan Reproduksi pada Komunitas Wanita Manjah Squads di Tangerang - Fadhil, Muhammad; Sari, Bunga Anggreini; Sukrisno, Adi; Razi, Fakhri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
This community service activity aimed to evaluate the effectiveness of an educational program in improving knowledge about menopause among adult women. The background was based on findings that the majority of women feel unprepared to face the menopausal transition due to significant knowledge gaps. The method employed was a single educational intervention in the form of a seminar, followed by knowledge assessment through pre-test and post-test. The participants consisted of nine women aged 35–54 years from the